REAL-TIME NETWORK TRAFFIC ANALYSIS USING RECURRENT NEURAL MODELS: REAL-TIME NETWORK TRAFFIC ANALYSIS USING RECURRENT NEURAL MODELS - Denev, Daniel; Staneva, Liliya (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
With the increasing complexity and dynamics of modern computer networks, there is a need for methods that can provide timely and accurate analysis of network traffic. Traditional techniques for monitoring and anomaly detection are often limited by static rules and the inability to capture complex time dependencies. In this context, recurrent neural networks (RNNs), and in particular their advanced architectures such as LSTM and GRU, appear as promising tools for real-time analysis. This article reviews the application of recurrent neural models for prediction, classification and anomaly detection in network traffic, focusing on architectural features, challenges and potential directions for development.